2009
DOI: 10.1007/s10875-009-9305-9
|View full text |Cite
|
Sign up to set email alerts
|

Local and Systemic Activation of the Mononuclear Phagocyte System in Aseptic Loosening of Total Hip Arthroplasty

Abstract: Taken together, our results demonstrate the integrated activation of the MPS and suggest the possible use of cytokines in the laboratory workup of prosthesis aseptic loosening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…The titanium samples mimick the real state occurring in the periprosthetic region, which was derived from the implants in vivo. 48 The figure shows that similar levels of osteoclasts were reached when cultured in the extracts of Ti, TiO 2 , and AT-TiO 2 . Fig.…”
Section: Osteoclast Activitymentioning
confidence: 76%
“…The titanium samples mimick the real state occurring in the periprosthetic region, which was derived from the implants in vivo. 48 The figure shows that similar levels of osteoclasts were reached when cultured in the extracts of Ti, TiO 2 , and AT-TiO 2 . Fig.…”
Section: Osteoclast Activitymentioning
confidence: 76%
“…Activation of the monocyte-macrophage-system leads to a local inflammatory reaction and is a relevant promoter for prosthetic loosening [6]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that localized peri-implant bone loss might be reflected at the systemic level 29,30 . Synovial fluid analyses have provided information on biochemical changes in the joint 31 . However, the usefulness of joint aspirate as a matrix for biomarkers is a matter of debate 32 .…”
Section: Discussionmentioning
confidence: 99%